The effects of 0.16 % Chromium + 1.32 % Nickel addition on austempered ductile Iron for mechanical properties and slurry erosion / Bulan Abdullah ... [et al.] - Abdullah, Bulan; Muhammad Yusof, Khalissah; Saad, Nor Hayati; Mokhtar, Ahmad Syazni (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
The effects of mechanical properties and slurry erosive wear behaviour on combination of Chromium and Nickel Alloyed Ductile Iron before and after austempering process were investigated in this study. Specimens of pure ductile iron and addition of 0.16 % Cr+ 1.3 2% Ni alloyed ductile iron were produced through conventional CO2 sand casting method. The specimens were then austenitized at 900 0C before being tempered at 300 0C for 40 minutes. The slurry erosion of newly developed material were obtained by means of slurry erosive wear and the mechanical testing involved tensile test (TS 138 EN1002-1), Vickers hardness test and Charpy Impact test (ASTM E23). Roughness tests as well as SEM observations were also done to Cr-Ni alloyed ductile iron samples. All the testing was done to both as cast and austempered specimens. Austempering process heat treatment of Cr-Ni alloyed ductile iron has shown an increase in slurry wear and mechanical properties compared to as cast due to solid strengthening effect of Chromium and Nickel. Meanwhile, the austempering process does improve the hardness of alloyed ductile iron.